Fish trade in Medieval North Atlantic societies : an interdisciplinary approach to human ecodynamics - Dufeu, Val (Early medieval North Atlantic., 2018)
Val Dufeu here reconstructs settlement patterns of fishing communities in Viking Age Iceland and proposes socio-economic and environmental models relevant to any study of the Vikings or the North Atlantic. She integrates written sources, geoarchaeological data, and zooarchaeological data to examine how fishing propelled political change in the North Atlantic. The evolution of survival fishing to internal fish markets to overseas fish trade mirrors wider social changes in the Vikings? world.